3(3y-3)-16=4(2y+5)-10

Simple and best practice solution for 3(3y-3)-16=4(2y+5)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3y-3)-16=4(2y+5)-10 equation:



3(3y-3)-16=4(2y+5)-10
We move all terms to the left:
3(3y-3)-16-(4(2y+5)-10)=0
We multiply parentheses
9y-(4(2y+5)-10)-9-16=0
We calculate terms in parentheses: -(4(2y+5)-10), so:
4(2y+5)-10
We multiply parentheses
8y+20-10
We add all the numbers together, and all the variables
8y+10
Back to the equation:
-(8y+10)
We add all the numbers together, and all the variables
9y-(8y+10)-25=0
We get rid of parentheses
9y-8y-10-25=0
We add all the numbers together, and all the variables
y-35=0
We move all terms containing y to the left, all other terms to the right
y=35

See similar equations:

| v3+ 4.5=7.61 | | -3f=-5f-18 | | (5-x)2+64=10 | | 3x+5+4=14 | | )2x-5(x-3)=2(x-10+ | | 20-13r=9-6r+4 | | −5x+8=−4x+9 | | 3-x+8+4x-4=2+3x+9 | | -2+5x-7=3x-9 | | 7x+13x-8=4(5x+9) | | 18x+10=x+2 | | 8.2=4.2+2h | | |3x-5|+4=14 | | 11z-1=12z-14 | | 1/4r=16 | | -15p=17-14p | | 2x+4=7x-4 | | -7.8c=1.56 | | 6/4+2p=-2/p-10 | | .-12+6x=6+5(X-2) | | -45=36x-20 | | 4.7/18.6=x/4 | | 18x-7=-5x-19 | | 33=12c-3(9-c) | | 1.4-(t+6=4.6 | | 33=12c-3(9-c | | m/4=7.3 | | 2/3x-25=29 | | 11.5u=0.13+11.4u | | -16x+4=6x-9 | | 5+20-5x(6-3)=x | | 2.5*4+5y=20 |

Equations solver categories